2022
DOI: 10.2147/idr.s374826
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mycobacterium tuberculosis RNA Accuracy in Various Respiratory Specimens for the Rapid Diagnosis of Pulmonary Tuberculosis

Abstract: Objective To evaluate the rapid diagnostic accuracy of Mycobacterium tuberculosis RNA (TB-RNA) for pulmonary tuberculosis (PTB) in a large patient sample and to evaluate the difference in TB-RNA diagnostic accuracy in various respiratory specimens. Methods Patient medical records were retrospectively reviewed to determine the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the curve (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Acid-fast staining relies on the high number of bacteria present in the sputum to give accurate results. Several studies have shown that the sensitivity of acid-fast staining can be as low as 8% or as high as 55.68% ( Qiu et al., 2022 ; Stadelman et al., 2022 ; Uddin et al., 2022 ; Zhang et al., 2022 ). Although mNGS is slightly more sensitive than T-SPOT.TB assay, for TB, a trade-off from a cost/time perspective would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Acid-fast staining relies on the high number of bacteria present in the sputum to give accurate results. Several studies have shown that the sensitivity of acid-fast staining can be as low as 8% or as high as 55.68% ( Qiu et al., 2022 ; Stadelman et al., 2022 ; Uddin et al., 2022 ; Zhang et al., 2022 ). Although mNGS is slightly more sensitive than T-SPOT.TB assay, for TB, a trade-off from a cost/time perspective would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…TB-RNA testing was performed using simultaneous amplification and testing (SAT) method ( Qiu et al, 2022 ) according to the manufacturer’s instructions (Shanghai Rendu Biological Technology Co., Ltd., China). All samples were diluted with 4% NaOH solution.…”
Section: Methodsmentioning
confidence: 99%
“…12 The application of MTB-RNA detection for TB mainly focuses on the auxiliary diagnosis of PTB and is limited to EPTB application. 13 , 14 However, the application of MTB-RNA for the rapid diagnosis of LNTB remains to be established; moreover, the diagnostic accuracy of this method for LNTB is unclear. In addition, the difference in the diagnostic efficacy of MTB-RNA using different specimens is unknown because of the multiple specimens that can be obtained for LNTB.…”
Section: Introductionmentioning
confidence: 99%